CYCLOMORPHOSIS IN THE EVOLUTION OF HELIOLITOIDEA CORALS: EVIDENCE AND SIGNIFICANCE - Bondarenko O.B. (My University, 2003)
The cyclic growth of Heliolitoidea corals is expressed in periodic changes in their morphometric characteristics at the transition from the light zone to the dark zone of the cycle. Genera and higher taxa experience morphological changes; species are liable to metric changes. General evolutionary processes are related to the dark zones of cyclomorphosis. A new genus Eumiklites and its type species E. strictus sp. nov. from the Tsagan Bulak Beds (lower Ludlovian) of southern Mongolia are described.